1998
DOI: 10.1002/(sici)1096-9861(19980105)390:1<133::aid-cne11>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Organization of diencephalic projections from the medullary subnucleus reticularis dorsalis and the adjacent cuneate nucleus: A retrograde and anterograde tracer study in the rat

Abstract: The distribution and organization of diencephalic projections from the subnucleus reticularis dorsalis (SRD) and the neighbouring cuneate nucleus (Cu) were studied in the rat by using microinjections of Phaseolus vulgaris leucoagglutinin in SRD and Cu and wheat germ agglutinin-apo horseradish peroxidase-gold in some selected thalamic areas. As previously reported, the efferent projections from the Cu were essentially contralateral and terminated mainly in the ventroposterolateral thalamic nucleus. Less dense t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 86 publications
3
52
4
Order By: Relevance
“…The following nuclei receive spinothalamic afferents and have been reported to contain nociceptive neurons (above and Ammons et al 1985) and project to cingulate cortex: Pf, centrolateral (Cl), paracentral (Pcn), reuniens (Re), paraventricular (Pv), central, ventromedial (VM), parvocellular mediodorsal (MDpc), and limitans (Li). In addition, the parabrachial nucleus and SRD contain nociceptive neurons and project to Re, Pf, VM (Menendez et al 1996;Pritchard et al 2000;Villanueva et al 1988Villanueva et al , 1998 and, as noted, each of them project to cingulate cortex. Evidence of direct nociceptive transmission via MITN arises from lidocaine injections into the Pf that block such activity (Sikes and Vogt 1992).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The following nuclei receive spinothalamic afferents and have been reported to contain nociceptive neurons (above and Ammons et al 1985) and project to cingulate cortex: Pf, centrolateral (Cl), paracentral (Pcn), reuniens (Re), paraventricular (Pv), central, ventromedial (VM), parvocellular mediodorsal (MDpc), and limitans (Li). In addition, the parabrachial nucleus and SRD contain nociceptive neurons and project to Re, Pf, VM (Menendez et al 1996;Pritchard et al 2000;Villanueva et al 1988Villanueva et al , 1998 and, as noted, each of them project to cingulate cortex. Evidence of direct nociceptive transmission via MITN arises from lidocaine injections into the Pf that block such activity (Sikes and Vogt 1992).…”
Section: Introductionmentioning
confidence: 79%
“…The Pf likely contributes to descending pain control, since it projects to the periaqueductal gray (Sadikot et al 1992) and electrical stimulation of the Pf generates mainly excitatory responses therein as does noxious heat or pressure stimulation of the skin (Sakata et al 1988). Nociceptive afferents are transmitted from the spinal cord (Willis et al 1979;Apkarian and Hodge 1989), subnucleus reticularis dorsalis (SRD; Bernard et al 1990;Villanueva et al 1998) and the parabrachial (Royce et al 1991;Bester et al 1999;Pritchard et al 2000) nuclei to the MITN and each of these nuclei project in turn to cingulate cortex (Minciacchi et al 1986;Royce et al 1989). The following nuclei receive spinothalamic afferents and have been reported to contain nociceptive neurons (above and Ammons et al 1985) and project to cingulate cortex: Pf, centrolateral (Cl), paracentral (Pcn), reuniens (Re), paraventricular (Pv), central, ventromedial (VM), parvocellular mediodorsal (MDpc), and limitans (Li).…”
Section: Introductionmentioning
confidence: 99%
“…The following subcortical structures have been found to project to CM: the mesencephalic, pontine, and medullary reticular formation, the serotonergic dorsal raphe, median raphe and raphe magnus, the cholinergic PPT and LDT nuclei, the nucleus prepositus hypoglossi, the spinal trigeminal nucleus, the medial and lateral vestibular nuclei, the parabrachial complex, the LC, nucleus incertus, distinct regions of the PAG, deep layers of the SC, the nucleus of Darkschewitsch, and the pars reticulata and pars compacta of the substantia nigra (Peschanski and Besson, 1984; Jones and Yang, 1985; Vertes et al, 1986, 1999, 2010; Yamasaki et al, 1986; Hallanger et al, 1987; Vertes and Martin, 1988; Vertes, 1991; Villanueva et al, 1998; Bester et al, 1999; Groenewegen et al, 1999; Shiroyama et al, 1999; Goto et al, 2001; Krout and Loewy, 2000a, 2000b; Krout et al, 2001, 2002; Olucha-Bordonau et al, 2003). In addition, CM receives input from deep cerebellar nuclei, the supramammillary nucleus, zona incerta, and the reticular thalamic nucleus (Haroian et al, 1981; Vertes, 1992; Kolmac and Mitrofanis, 1997; Power et al, 1999; Power and Mitrofanis, 2001).…”
Section: The Limbic Thalamusmentioning
confidence: 99%
“…The midline and intralaminar thalamic nuclei contain nociceptive neurons (Casey, 1966;Dong et al, 1978) and receive spinothalamic input including the reuniens, parafascicular (Pf) and periventricular nuclei (Mantyh, 1983). Ammons et al (1985) showed that viscerocutaneous spinothalamic tract neurons project to the medial thalamus including the parafascicular and centrolateral nuclei and these nuclei receive input from the pronociceptive subnucleus reticularis dorsalis (Villanueva et al, 1998) as does the parabrachial nucleus (Bester et al, 1999). Both of these latter nuclei respond to visceral and cutaneous nociceptive stimulation (Roy et al, 1992;Villanueva et al, 1989).…”
Section: Source and Latency Of Visceral Nociceptive Signalmentioning
confidence: 99%
“…In terms of cutaneous-only processing, such input could arise from nucleus cuneatis projections to Pf and reuniens if this channel remained selective (Villanueva et al, 1998). Along the same line, there may be some thalamic nuclei that receive preferential cutaneous input and do not project to ACC but do project to MCC and dorsal PCC.…”
Section: Source and Latency Of Visceral Nociceptive Signalmentioning
confidence: 99%